Education, job search and re-employment outcomes among the unemployed - W. Craig Riddell; Xueda Song (Institute for the Study of Labor (IZA), 2011)
This study assesses the effects of education on both job search intensity and re-employment success for unemployed workers. Given that the positive correlation between education and job search intensity or re-employment success is likely to be confounded by the endogeneity of education, we make use of data on compulsory schooling laws to create instrumental variables to assess the causal effects of education. Based on data from the Labour Force Survey and the Canadian Census, we find that education both significantly increases job search intensity and significantly improves re-employment success for the unemployed. The evidence on job search intensity provides insights into one potential mechanism through which education may increase the probability of re-employment following unemployment.
urn:nbn:de:101:1-201112136867
Keywords: I21; J64; 330; education; adaptability; unemployment; job search; causal effects; compulsory schooling laws; Arbeitslosigkeit; Arbeitsuche; Bildungsniveau; Berufliche Integration; Schätzung; Kanada